How to reach people who do not want to be reached: psychosocial counseling for school-dropouts in vocational training - Möhring, Julian Valentin; Wölfel, Méline; Brosig, Burkhard (Frontiers in Psychology, 2023)
Emerging adulthood (Arnett 2004) without vocational training concerns young people from difficult social backgrounds who are often not adequately reached by therapeutic help. Difficult and traumatic experiences with therapeutic institutions are common to many of these young people in addition to a long lasting, unsatisfying patient-career. Without professional support from the therapeutic field, vocational qualification measures often cannot meet the needs of young people with inner conflicts. A counseling center for people with mental health problems was set up in 2010 as a link between professional support and a therapeutic setting. This article critically examines the importance of counseling for improving the personal situation of participants in vocational qualification measures on a descriptive level. We take a perspective on identity development and defense mechanisms in the thought of Vaillant and Erikson. Both theories focus on the social embeddedness of psychological processes. This theoretical background helps to understand young peoples' situations and difficulties. The unique setting of the counseling center that aims to match the particular needs of these young people is presented. Thus a low-threshold, destigmatising and flexible setting should provide better access to psychosocial support for participants in vocational qualification measures. Opportunities and limits of the concept are discussed.